Thyroid Disease and Anaemia Among Early Pregnant Iraqi Women - Wassan Nori; Alaa Ibrahim Ali; Roaa Mokram Hamed (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims: Iron deficiency anaemia and thyroid disease are common obstetrical problems. Both cause a wide range of complication, empathizing feto-maternal wellbeing. We verify iron deficiency anaemia effect on thyroid hormones during the first trimester. Methods: A cross-sectional study at Al-Yarmouk Teaching Hospital enrolled 100 primigravidae in their first trimester of a singleton pregnancy. Participants were subdivided into anaemic cases (50/100) and healthy controls (50/100) based on serum haemoglobin. We evaluated serum haemoglobin, ferritin, iron, Total Iron-Binding Capacity (TIBC)and T3, FT4, and TSH for all. Results: Both groups were comparable in age, body mass index, and gestational age. Higher serum levels of haemoglobin, ferritin, iron TSH, T3 were seen in the healthy controls versus anaemic cases; all differences were meaningful. Only TIBC and serum FT4 was significantly higher in anaemic cases. The ROC curve highlighted the validity of study markers in diagnosing anaemia. Serum iron was the most sensitive blood indices associated with anaemia, followed by ferritin, with a sensitivity of 94%, 84%, respectively. Conclusion: Thyroid disorders were very common in anaemic patients. As a result, women’s iron levels must be enhanced, and thyroid disease screening can begin early in pregnancy. Screening for both will unravel hidden differences and improve pregnancy outcome.